Immunogold electron microscopy of phytochrome in Avena: identification of intracellular sites responsible for phytochrome sequestering and enhanced pelletability (The Rockefeller University Press, 1986)
Using monoclonal antibodies to the plant photoreceptor, phytochrome, we have investigated by immunogold electron microscopy the rapid, red light-induced, intracellular redistribution (termed "sequestering") of phytochrome in dark-grown Avena coleoptiles. Pre-embedding immunolabeling of 5-micron-thick cryosections reveals that sequestered phytochrome is associated with numerous, discrete structures of similar morphology. Specific labeling of these structures was also achieved by post-embedding ("on-grid") immunostaining of LR-White-embedded tissue, regardless of whether the tissue had been fixed chemically or by freeze substitution. The phytochrome-associated structures are globular to oval in shape, 200-400 nm in size, and are composed of amorphous, granular material. No morphologically identifiable membranes are present either surrounding or within these structures, which are often present as apparent aggregates that approach several micrometers in size. An immunogold labeling procedure has also been developed to identify the particulate, subcellular component with which phytochrome is associated in vitro as a consequence of irradiation of Avena coleoptiles before their homogenization. Structures with appearance similar to those identified in situ are the only components of the pelletable material that are specifically labeled with gold. We conclude that the association of phytochrome with these structures in Avena represents the underlying molecular event that ultimately is expressed both as red light-induced sequestering in vivo and enhanced pelletability of phytochrome detected in vitro.